Pengembangan LKS Berbasis Etnomatematika Dengan Pendekatan Saintifik Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Heny Nugroho; Aprilia Nurul Chasanah; Megita Dwi Pamungkas (Jurnal Karya Pendidikan Matematika, 2022)
This study aims to determine the validity, practicality, and effectiveness of ethnomathematical-based worksheets with a scientific approach to improve students' mathematical problem solving abilities. The research type used is research and development with the ADDIE model. The validity test was carried out by using validator assessment data, the practicality test used a student response questionnaire, and the effectiveness test used a description test which was analyzed using N-Gain. The results showed that the worksheets developed were in the "Very Valid" category with a percentage score of 87%. Practicality test of LKS are "Very Practical" with a percentage score of 93%. The results of the LKS effectiveness test show an N-Gain score of 0.57 (Medium category) in improving student’s mathematical problem solving abilities (effectiveness criteria). It can be concluded that the ethnomathematics-based worksheets with a scientific approach to improve student's mathematical problem solving skills are valid, practical, and effective.